Domains and levels of physical activity are linked to adult mental health and wellbeing in deprived neighbourhoods: A cross-sectional study. (October 2016) - Mason, Phil; Curl, Angela; Kearns, Ade
Abstract: Although relationships between participating in physical activity (PA) and positive mental health and wellbeing are well established, little is known about the relative contributions of the different domains of PA —household, occupational, active travel, leisure and sport, family activities— to total PA and, in turn, to mental health and wellbeing. This is particularly important for deprived communities where PA is low and mental health and wellbeing poor. Using multivariate multilevel regression of cross-sectional survey data collected in 2011, we examined self-reported PA levels and the domains and diversity of sources of PA among 2654 residents of 32 deprived neighbourhoods in Glasgow, UK, and their associations with measures of mental health, positive mental wellbeing, and physical and general health. Household chores and active travel were the most commonly cited PAs. People achieving PA from family activities, and those doing more diverse PAs, had better mental wellbeing. Active travel was associated with better mental wellbeing and mental health among the highly and moderately physically active, respectively. Highly active people who engaged in leisure-based PA had better mental health. Long-standing illness was associated with worse health scores, although mental wellbeing was ameliorated amongst those who did domestic or occupational PA. It is important to encourage greater diversity of PA in disadvantaged areas, including leisure and family activities and active travel for those out of work with low PA. Nevertheless, interventions aimed at managing long-term health conditions and providing employment may be of even greater importance. Highlights: Household chores & active leisure are the commonest physical activity (PA) sources. PA through leisure, active travel & family activities aid mental health and wellbeing. Chores and occupational PA ameliorate lower mental wellbeing in the long-term ill. Diversity of PA is associated with higher PA and better mental health and wellbeing.